Sustainable Harmony: Implications of Climate Change on Ecoculture in the Context of the Halal Industry - Ridhzha, Abu Sya’ban; Razali, Ramadhan (Institut Agama Islam Negeri Lhokseumawe, 2025)
This study examines the implications of climate change on ecoculture within the context of the halal industry, with a focus on ecological sustainability and halal practices. The research employs a qualitative approach using a literature review model. It analyzes the impact of climate change on halal raw material production, the adoption of environmentally friendly practices, socio-economic challenges, shifts in consumer preferences, and relevant policies. The findings reveal that climate change affects the supply chain and sustainability of the halal industry, compelling producers to innovate through eco-friendly technologies and sustainable production methods. This study also highlights the interconnection between halal principles and ecological sustainability goals, as well as the potential for their integration to create more environmentally friendly halal business models. These findings underscore the importances of cross-sector collaboration to address challenges and maximize sustainability potential within the halal industry.